An analysis of external stakeholders in higher education institutions: The schools’ identification and assessment of the stakeholders’ impact - Piotrowska-Piątek, Agnieszka (Journal of Public Governance, 2018)
The paper discusses the issue of cooperation of higher education institutions (HEIs) with their environment. Its main aim is to identify HEIs’ external stakeholders and to determine the importance that HEIs give them. The Author discusses this problem by analyzing the literature and the results of her own survey among rectors of HEIs. In light of the presented results, HEIs give the stakeholder status to many entities from their environment. Evaluation of their importance makes it possible to map them by dividing them into strategic, important, and others stakeholders.